A taxonomic revision of Chinese Boesenbergia (Zingiberaceae), with a new record - Chen, Juan; Xia, Nian-He (Phytotaxa, 2019)
The taxonomic history of Boesenbergia (Zingiberaceae) in China is reviewed. Based on field observations and herbarium specimen studies, a comprehensive taxonomic revision of Chinese Boesenbergia is carried out. The results suggest that those specimens previously misidentified as B. longiflora and B. fallax in China should be either B. maxwellii or B. kingii. Boesenbergia maxwellii is newly recorded for the country. Altogether, four species are recognized for China. Keys, descriptions, distributions and illustrations of all recognized species are presented.